Comparison of explosion puffing drying with other methods on the physicochemical properties and volatiles of yam (Dioscorea opposita thunb.) chips through multivariate analysis. Issue 7 (10th June 2022) - Gao, Qi; Chen, Jia-Nan; Zhang, Jian-Chao; Liu, Chun-Ju; Li, Da-Jing; Liu, Chun-Quan; Tanokura, Masaru; Xue, You-Lin
Abstract: Crisp yam chips were produced using hot air drying (AD), vacuum drying (VD), freeze drying (FD), and explosion puffing drying (EPD). As a result, the reducing sugar, total polyphenol and vitamin C contents, rehydration rate and volume ratio were well retained in freeze-dried chips with explosion puffing-dried chips following closely behind, which exhibited a higher total soluble solids content (TSS) and crispness. The microstructure of explosion puffing-dried chips showed distinct cell wall breakage and cell expansion, indicating the release of more TSSs and a relatively high hardness and crispness. Based on physicochemical chip properties, FD and EPD could be distinguished from the other drying methods, and the characteristic physicochemical properties of explosion puffing-dried yam chips were identified as the hardness and TSS level using multivariate analysis. Furthermore, 43 volatile compounds were isolated and identified in fresh yam and dried yam chips using headspace solid-phase microextraction gas chromatography-mass spectrometry (HS-SPME-GC-MS). Based on the volatile compositions of the samples, oct-1-en-3-ol was identified as the major volatile compound in fresh yam, and the volatiles in the explosion puffing-dried chips were clearly distinguished from those in the other dried yam chips due to the unique puffing process.